2006
DOI: 10.1016/j.aquaculture.2005.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic efficacy of tricaine methanesulfonate, metomidate and eugenol: Effects on plasma cortisol concentration and neutrophil function in fathead minnows (Pimephales promelas Rafinesque, 1820)

Abstract: Anesthetic efficacy, plasma cortisol concentration, and two parameters of neutrophil function (oxidative burst and degranulation of primary granules) were compared among three anesthetics in the fathead minnow: tricaine methanesulfonate (MS 222), metomidate hydrochloride (MTMD), and eugenol (EUG). The optimum anesthetic concentration was determined as: MS 222 75 mg L − 1 , EUG 30 mg L − 1 and MTMD 4 mg L − 1 . Handling and crowding stress was induced in fish with (SA) and without (S) anesthetic. Plasma cortiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
4
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 33 publications
(73 reference statements)
8
87
4
4
Order By: Relevance
“…Inhibition of the immunosuppressive effect of handling stress (lymphopenia, neutrophilia, and reduction of phagocyte oxidative metabolic activity) in carp juveniles sedated with etomidate was also observed in our previous study (18). Palic et al (30) reported that metomidate prevented stressinduced decrease of neutrophil function in Pimephales promelas, while MS-222 did not. Ortuno et al (21) found that tricaine did not suppress respiratory burst and other phagocyte functions in Sparus aurata.…”
Section: Discussionsupporting
confidence: 81%
“…Inhibition of the immunosuppressive effect of handling stress (lymphopenia, neutrophilia, and reduction of phagocyte oxidative metabolic activity) in carp juveniles sedated with etomidate was also observed in our previous study (18). Palic et al (30) reported that metomidate prevented stressinduced decrease of neutrophil function in Pimephales promelas, while MS-222 did not. Ortuno et al (21) found that tricaine did not suppress respiratory burst and other phagocyte functions in Sparus aurata.…”
Section: Discussionsupporting
confidence: 81%
“…In the same study, higher plasma cortisol concentrations were found in benzocaine-exposed fish as compared to those exposed to eugenol (Iversen et al, 2003). In contrast to the present results, Palic et al (2006) reported no significant differences in plasma cortisol concentrations of fish anesthetized with MS-222, metomidate and eugenol (Palić et al,2006). In rainbow trout, no differences were observed in plasma cortisol levels between MS-222, eugenol, and CO 2 (Pirhonen et al, 2003).…”
Section: Discussioncontrasting
confidence: 70%
“…A variety of anesthetics such as tricaine methanesulphonate (MS-222), 2-phenoxyethanol, quinaldine, benzocaine, and metomidate have been used for this purpose (Ross & Ross, 2008). However, the use of some anesthetics has been limited or rejected due to undesirable side effects for fish and humans (Palic et al, 2006). Alternatively, several studies using plant derivative compounds, such as essential oils (EOs) from Eugenia, Mentha, and Lippia species, have demonstrated that these natural products are effective for fish sedation and may have benefits over traditional methods, including lower cost and higher safety (Cunha et al, 2010a;Gonçalves et al, 2008;Palic et al, 2006).…”
Section: Introductionmentioning
confidence: 99%